PEMODELAN PROSES BISNIS DENGAN BPMN (STUDI KASUS: DEPARTEMEN PROCUREMENT UNIVERSITAS ADVENT INDONESIA) - Elmor Benedict Wagiu (TeIKa, 2018)
Business Process Model and Notation, commonly known as BPMN, is a concept used to model a business process. Through the use of BPMN, the modeling of a business process in a business flow can be clearly and in detail. The relationship between entities and any activities that occur can be documented on a model that is designed. In the Procurement Department, many activities are carried out, including procurement of goods, purchasing procedures, inventory mechanisms, steps to purchase goods and other matters. All these activities in fact do not yet have a standard model that must be used as a reference in carrying out activities as exemplified above. Therefore, with the modeling using BPMN, the Procurement Department can have a standard guide to every business process that occurs.